"I believe…": A qualitative study of older adults. Issue 4 (2nd October 2017) - Stevens, Bruce A.
ABSTRACT: Beliefs. Believing. Both are tested by different life experiences. This qualitative study of 15 older adults used a grounded theology methodology to develop a model of what influences the views of a range of Christian and agnostic subjects. The study identified two sources in life learning and spiritual learning that influence agnostic, more liberal, or conservative beliefs. This emergent model is contrasted with the approach of leading theologian Graham Ward.